Dialogic Accountings for Stakeholders: On Opening Up and Closing Down Participatory Governance - Brown, Judy; Dillard, Jesse (Journal of Management Studies, 2015)
ABSTRACT Interpretivist and critical accounting researchers have long challenged the shareholder focus of conventional accounting, calling for new approaches that promote accountability to stakeholders and participatory governance. One proposal is for dialogic accountings that take pluralism seriously and enable critical reflection on organizational practices from diverse socio‐political perspectives. Dialogic accounting aims to counter narrow managerialist framings and address constituencies poorly served by traditional accounting. However, those favouring pluralist approaches face significant challenges in addressing entrenched ideologies and power relations. Rather than trying to address these challenges solely from within accounting, much can be learned from disciplinary fields that demonstrate sustained interest in pluralistic analysis and engagement. Here, we focus on the insights science and technology studies (STS) provides on opening up and closing down participatory governance, understanding knowledge‐power dynamics and implications for stakeholder value creation.